2019
DOI: 10.1042/bsr20190788
|View full text |Cite
|
Sign up to set email alerts
|

The microRNA in ventricular remodeling: the miR-30 family

Abstract: Ventricular remodeling (VR) is a complex pathological process of cardiomyocyte apoptosis, cardiac hypertrophy, and myocardial fibrosis, which is often caused by various cardiovascular diseases (CVDs) such as hypertension, acute myocardial infarction, heart failure (HF), etc. It is also an independent risk factor for a variety of CVDs, which will eventually to damage the heart function, promote cardiovascular events, and lead to an increase in mortality. MicroRNAs (miRNAs) can participate in a variety of CVDs t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
53
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 111 publications
0
53
0
2
Order By: Relevance
“…miR-30 was shown to be cardioprotective in heart failure inhibiting cardiomyocyte autophagy [46]. The miR-30 family is abundant in the heart and to participate in ventricular remodeling through autophagy, inflammatory pathways and apoptotic mechanisms [47]. miR-146a is known to be cardioprotective and to reduce infarct size in in vivo animal models of AMI [48].…”
Section: Discussionmentioning
confidence: 99%
“…miR-30 was shown to be cardioprotective in heart failure inhibiting cardiomyocyte autophagy [46]. The miR-30 family is abundant in the heart and to participate in ventricular remodeling through autophagy, inflammatory pathways and apoptotic mechanisms [47]. miR-146a is known to be cardioprotective and to reduce infarct size in in vivo animal models of AMI [48].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the miR-30 family is critical in regulating the expression levels of genes responsible for autophagy, apoptosis, oxidative stress, inflammation, and fibrosis, which are the pathological basis of LVH development [17][18][19] . Indeed, the role of miR-30 family in cardiomyocyte hypertrophy has been reported in cultured cells and animal studies 17,20,21 ; however, the significance of mir-30 family members in a clinical setting has not been evaluated so far.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanistically, the miR-30 family can inhibit autophagy and apoptosis, decrease inflammation, etc., thereby reducing collagen deposition and myocardial fibrosis, and preventing cardiac hypertrophy 19 . We thus detected the correlation between miR-30 family members and the circulating markers for inflammation (hs-CRP) and collagen synthesis (MMP-9).…”
mentioning
confidence: 99%
“…The NLRP3 inflammasome, specifically, is delivered to autolysosomes by autophagy biomarkers LC3 and P62 [13]. Additionally, miRs play an important role in regulating autophagy in many diseases, especially cardiovascular diseases [14][15][16]; however, further studies are needed to investigate the role of miRs in the response to endothelial cell inflammatory injury through end-stage autophagy.…”
Section: Introductionmentioning
confidence: 99%